Understanding Barack Obama’s Characteristics through “Dreams from My Father” - Ratini Setyowati (IAIN Salatiga, 2014)
Obama is not only popular as a president but also popular for his literary works. He has some literary works especially his popular books, such as Dreams from My Father: A Story of Race and Inheritance, the Audacity of Hope, Change We can Believe in and others. His books can insipre others. One of his popular book is Dreams from My Father: A Story of Race and Inheritance. In his book he tells everything about his life, his journey to some cities and countries. He describes them well and can hipnotize the readers. The purpose of the study is to know Obama‘s characteristic through his book Dreams of My Father: A Story of Race and Inheritance. This study is descriptive qualitative research, the method of the study is library research. The analyses and depictions in this studywill be taken from books, journals, magazines, and articles that are related to Barack Obama‘s book Dreams from My Father: A Story of Race and Inheritance, beside that to complete the data the writer takes the sources from internet. The result of the study is the book reflects the character of Obama. To analyze the study, the writer applies Psychoanalysis Approach (Id, Ego and Superego) Keywords: Dreams for my father; characteristics; race and inheritance